Role of Higher-Order Interactions on the Modulational Instability of Bose-Einstein Condensate Trapped in a Periodic Optical Lattice - Sabari, S. [UNESP]; Lekeufack, Ot; Yamgoue, Sb; Tamilthiruvalluvar, R.; Radha, R. (Springer Nature, 2022)
In this paper, we investigate the impact of higher-order interactions on the modulational instability (MI) of Bose-Einstein Condensates (BECs) immersed in an optical lattice potential. We derive the new variational equations for the time evolution of amplitude, phase of modulational perturbation, and effective potential for the system. Through effective potential techniques, we find that high density attractive and repulsive BECs exhibit new character with direct impact over the MI phenomenon. Results of intensive numerical investigations are presented and their convergence with the above semi analytical approach is brought out.